Antimicrobial use in agriculture: critical review of the factors influencing behaviour. Issue 4 (30th November 2021) - McKernan, C; Benson, T; Farrell, S; Dean, M
Abstract: Antimicrobial resistance (AMR) is a global health emergency affecting humans and animals, diminishing the effectiveness of medication used to treat illness. The agri-food sector has attracted increased attention for imprudent antimicrobial use (AMU) and its contribution to AMR. Thus, ascertaining farmers' and veterinarians' behaviours surrounding AMU is essential to address imprudent AMU and generate behaviour change within the agri-food sector. Therefore, the aim of this critical review is to investigate, assess and collate the current body of evidence to identify psychosocial factors including knowledge, understanding, perceptions, attitudes and behaviours surrounding AMU. Database searches were limited to articles utilizing qualitative and quantitative methodologies, available in English with no restriction on publication year. Of the 1156 articles identified, 103 were retained for this review. Findings on the psychosocial aspects were thematically analysed. Five key themes emerged from the data: (i) knowledge and awareness of antimicrobials; (ii) attitudes towards antimicrobials; (iii) influential relationships; (iv) resources; and (v) factors influencing AMU. Results indicated that to overcome barriers experienced by key stakeholders, a carefully considered, evidence-based approach, incorporating behaviour change theory, is required when designing intricate interventions/strategies, in order to elicit successful and sustained AMU behaviour change.